Molecular packing in organic anisotropic media: effects of piesothermal factors on optical transmission in polycrystalline samples - Minenko, S.S.; Tarasenko, O.A.; Budakovsky, S.V.; Lisetski, L.N.; Galunov, N.Z. (Functional Materials, 2009)
Optical transmission was measured for pellets made of polycrystalline powders of stilbene and p-terphenyl subject to pressure compaction at temperatures close to the melting point. As compared with similar samples obtained by compaction at room temperature, the transparence was substantially higher, with this difference being more pronounced at higher treatment temperatures and smaller grain size of the initial powder; also, the effect observed was noticeably stronger for trans-stilbene than for p-terphenyl. The obtained results can be explained in terms of local melting and liquid crystalline ordering of the molecules in outer layers of neighboring grains, resulting in more uniform structuring. Since the measured transparence of the samples showed good correlation with the luminescence light yield for short-range alpha-radiation, this approach can also be used as a method for express analysis of the pellet quality in experimental optimization of preparation conditions of polycrystalline organic scintillators. Досліджено оптичне пропускання для зразків полікристалічних порошків стильбену та п-терфенілу, які було піддано пресуванню при температурах, близьких до точки плавлення. У порівнянні з аналогічними зразками, пресованими при кімнатній температурі, пропускання значно збільшувалося, причому ця різниця зростала з підвищенням температури пресування і зменшенням розміру зерен. Цей ефект був помітно сильнішим для транс-стильбену у порівнянні з п-терфенілом. Отримані результати можна пояснити у термінах локального плавлення та рідкокристалічного впорядкування молекул у зовнішніх шарах сусідніх зерен. Оскільки прозорість зразків добре корелювала з світловим виходом люмінесценції для короткопробіжного альфа-випромінювання, цей підхід може бути використаний для експрес-аналізу якості пресованих зразків полікристалічних органічних сцинтиляторів. Исследовано оптическое пропускание образцов поликристаллических порошков стильбена п-терфенила, подверженных прессованию при температурах, близких к точке плавления. По сравнению с аналогичными образцами, запрессованными при комнатной температуре, пропускание значительно увеличивалось, причем это различие возрастало с повышением температуры и уменьшением размеров зерен. Данный эффект был заметно более выражен для транс-стильбена по сравнению с п-терфенилом. Полученные результаты интерпретируются в терминах локального плавления и жидкокристаллического упорядочения молекул во внешних слоях соседних зерен. Поскольку прозрачность образцов хорошо коррелирует со световыходом люминесценции для короткопробежного альфа-излучения, данный подход можно использовать для экспресс-анализа качества прессованных образцов поликристаллических органических сцинтилляторов.